(untitled) - Ondrus, Jan; Dicova, Jana (Doprava a spoje, 2012)
Innovative ideas contribute to successfully manage the impact of changing environment and to obtain greater competitiveness and contribute intentionally or accidentally discovered and implemented. The authors of innovative ideas are mainly people and these new ideas are then applicable in all areas, including transport.